Long fiber with skin-core structure, long fiber board and application
By using a core-sheath structure and a long fiber design, a cross-linked network is formed through the reversible reaction of furan groups and maleimide groups. This solves the problem of insufficient melting point of PET composite long fibers during heating, achieving a balance between high strength and toughness, making it suitable for components such as automotive underbody panels.
Patent Information
- Application Number
- CN202511291614.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-09-10
AI Technical Summary
The melting point of the low-melting-point fiber in the existing PET composite long fiber is not low enough when heated, so it cannot simultaneously achieve both low melting point and high mechanical strength, which makes the fiber orientation and properties easily damaged during the heating process.
The long fiber design with a core-sheath structure features a low melting point for the polyester sheath and a high melting point for the core. The sheath contains furan and maleimide groups that undergo a reversible Diels-Alder reaction to form a cross-linked network structure, which improves the mechanical properties of the fiber. It also re-crosslinks after depolymerization and melting upon heating.
It achieves a balance between low melting point and high mechanical properties. The fiber orientation is not damaged during the heating and molding process. After cooling, the mechanical properties are enhanced by chemical cross-linking between fibers. When applied to components such as automotive underbody panels, it has high strength, good toughness, and good sound absorption.
Smart Images

Figure CN120945524A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester fiber technology, specifically to a long fiber with a core-sheath structure, a long fiberboard, and its applications. Background Technology
[0002] Research on passenger car underbody protection panels began in the early 2000s. Some C-segment cars adopted underbody protection panels to improve aerodynamics. On the one hand, this reduces wind resistance and energy consumption; on the other hand, it protects chassis components, providing protection against scratches, impacts, corrosion, sound insulation, and dust. The initial underbody protection panels were formed using plastic parts GMT technology and LFT-D technology. With the soaring international oil prices and the increasing demand from automakers to continuously optimize energy consumption, the application of aerodynamic underbody protection panels was extended to A-segment cars, and lightweight modifications to the underbody protection panels began.
[0003] The development of lightweight underbody protection materials has progressed through stages: steel plate-glass fiber reinforced plastic and alloy plastic-fiber molded materials. Fiber molded underbody protection primarily uses lightweight reinforced thermoplastic plastics, made from a mixture of polypropylene and glass fibers to form felt or sheets. Polypropylene fibers are low-melting-point fibers, while glass fibers are high-melting-point reinforcing fibers. When heated, the melted felt is bonded to 50-80mm long glass fibers and then molded. Underbody protection materials produced by this method have a low density, being 30%-50% lighter than plastic underbody protection materials. However, they suffer from insufficient toughness and a risk of cracking in harsh wading conditions. In recent years, fiber molded underbody protection materials based on PET composite long fibers have developed rapidly. Compared to polypropylene glass fiber felt, they offer advantages such as lightweight, environmental friendliness, high strength, good toughness, good acoustic performance, and high cost-effectiveness.
[0004] PET long fibers are continuous composite fibers produced by extruding two PET melts with different properties from the same spinneret. The fiber cross-section exhibits a core-sheath structure, with low-melting-point PET forming the sheath and high-melting-point PET forming the core. When PET composite long fiber felt is heated, the low-melting-point PET melts into a high-viscosity liquid, solidifying into a fiber web upon cooling. The high-melting-point PET core layer retains its reinforcing fiber properties, ensuring the uniformity of the fiber web during heating and stretching. However, currently, low-melting-point PET still faces technical challenges, including a limited number of commercially available grades, insufficiently low melting points, and the inability to simultaneously achieve both low melting point and high mechanical strength. Summary of the Invention
[0005] To overcome the shortcomings of the existing technology, the present invention provides a long fiber with a core-sheath structure, a long fiberboard, and its application. The long fiber with a core-sheath structure provided by the present invention has a low melting point of the sheath and a high melting point of the core. When heated with steam, the sheath can melt without damaging the orientation and properties of the core fiber. Furthermore, the furan groups and maleimide groups of the sheath can undergo a reversible Diels-Alder reaction, forming a cross-linked network structure upon cooling, which improves the mechanical properties of the long fiber. Upon heating, it depolymerizes and melts, and upon cooling, it re-reacts between the composite long fibers to form a new cross-linked structure, greatly improving the degree of cross-linking and mechanical properties between the fibers, while balancing low melting point and high mechanical properties.
[0006] The present invention aims to provide a long fiber with a core-sheath structure, comprising a polyester sheath and a polyester core. The polyester sheath, by weight, comprises 100 parts modified polyester and 0-5 parts colorant. The modified polyester is obtained by polymerization of a diacid monomer and a polyol monomer in a molar ratio of 1:(1.0-1.5). The diacid monomer includes one or more of terephthalic acid and isophthalic acid. The polyol monomer, by molar weight, comprises 70-110 parts ethylene glycol, 2-10 parts a polyol having 3-6 hydroxyl groups, 5-10 parts maleimide diol, and 5-10 parts furan diol. The structural formula of the maleimide diol is shown in Formula 1, and the structural formula of the furan diol is shown in Formula 2.
[0007]
[0008] The polyester core layer comprises the following components by weight: 80-100 parts PET, 10-20 parts PEN, 0.1-1 parts nucleating agent, and 0-5 parts colorant.
[0009] In one specific embodiment, the mass ratio of the cortex to the core is 1:(3-5).
[0010] In one specific embodiment, the nucleating agent is at least one of talc, organic amides, and hydroxyalkyl metal salts; the colorant is carbon black; and the polyol is selected from at least one of glycerol, pentaerythritol, xylitol, dipentaerythritol, and sorbitol.
[0011] In one specific embodiment, the PET core layer has a melting point ≥250°C.
[0012] In one specific embodiment, the maleimide diol is prepared by condensing 2-maleiminoacetic acid and 3-amino-1,2-propanediol in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS).
[0013] In one specific embodiment, the furan glycol is prepared by reacting pre-dried furfurylamine and glycidyl ether at 25–50°C for 2–24 hours.
[0014] In one specific embodiment, the modified polyester is prepared as follows: diacid and polyol are added to a reaction vessel in a certain proportion, stirred evenly, and then heated to 170-190°C for esterification reaction. The reaction lasts for 8-10 hours. When the acid value drops to 50-80 mg KOH / g, the esterification reaction is considered to be basically completed. The reaction temperature is gradually increased to 260-280°C, and the vacuum system is started simultaneously to slowly reduce the pressure inside the reaction vessel to below 10 Pa for polycondensation reaction. When the intrinsic viscosity reaches 0.35-0.8 dL / g, the reaction is stopped, nitrogen gas is introduced to atmospheric pressure, and the molten polyester is extruded through a gear pump, granulated by a pelletizer, and dried to obtain the modified polyester.
[0015] This invention also protects a method for preparing a long fiber with a core-sheath structure, comprising the following steps:
[0016] S1. The polyester skin material and the polyester core material are melt-extruded separately in a twin-screw extruder to obtain polyester skin chips and polyester core chips, which are then pre-dried.
[0017] S2. The polyester sheath chips are melted in a screw extruder at 160-250℃, with the melt pressure controlled at 8-12MPa. The polyester core chips are melted in another extruder at 260-270℃, with the melt pressure controlled at 10-15MPa. After filtration, the two melts are fed into the composite spinning assembly with precise flow control through a metering pump. After being combined into a concentric structure in the spinneret orifice, they are extruded to form nascent fibers with a diameter of 50-100μm.
[0018] S3. The nascent fibers are rapidly cooled to 80-100℃ by side blowing air to solidify the core-sheath structure, and then enter the stretching machine for multi-stage stretching at 80-120℃, with a total stretching ratio of 3-5 times.
[0019] S4. Finally, heat set in an oven at 120-180℃ and wind at a speed of 3000-5000m / min to obtain long fibers with a core-sheath structure.
[0020] This invention also protects a long fiberboard, which is produced by compression molding of the long fibers having a core-sheath structure, wherein the areal density of the long fiberboard is 1200–1600 g / m³. 2 .
[0021] The present invention also protects the method for preparing the long fiberboard, comprising the following steps: long fibers with a core-sheath structure are arranged in a transverse and longitudinal manner to form a felt, which is then fed to a mold and clamped by a heated mold. Steam at 1.4 to 1.8 MPa is introduced to quickly penetrate the fibers, and the mold is opened after holding the pressure for 8 to 15 seconds. The long fiberboard is then removed, cooled, and punched.
[0022] The present invention also protects the use of the long fibers and the long fiber sheets in automobile body underbody panels, engine compartment underbody panels, battery underbody panels, mudguards, trunk trim panels, and front trunk panels.
[0023] Beneficial effects
[0024] This invention provides a long fiber with a core-sheath structure, a long fiberboard, and its applications. The long fiber with a core-sheath structure provided by this invention includes a low-melting-point polyester sheath and a high-melting-point polyester core. The modified polyester used in the polyester sheath introduces polyols, furan glycols, and maleimide glycols with 3-6 hydroxyl groups into the conventional PET polyester molecular structure, forming a molecular chain structure with branched segments and side chains. This disrupts the regularity of the original terephthalic acid and ethylene glycol molecular chains, thereby reducing the crystallinity and melting point of the polyester. Furthermore, the furan groups of the modified polyester have a diene structure, and the maleimide groups have a carbon-carbon double bond diene-loving structure. At temperatures below 100°C, the double bonds of furan and the C=C double bonds of maleimide undergo a [4+2] cycloaddition Diels-Alder reaction, forming a six-membered cyclic adduct. This increases the crosslinking density of the long fiber polyester sheath at room temperature, matching the high crystallinity and high melting point mechanical properties of the polyester core, resulting in a single fiber strength greater than 3 cN. When long fiberboard is prepared by steam heating and molding, the temperature rises above 120℃. At this temperature, a reverse Diels-Alder reaction occurs under the adduct, and furan and maleimide groups are released again, causing the polyester skin to melt rapidly. After demolding and cooling, the polyester skins of the long fibers melt and bond together. At the same time, the furan and maleimide groups at the interface of the composite long fibers undergo a new Diels-Alder reaction and crosslink. This allows the polyester skins of different long fibers to not only be physically melted and then cooled and solidified, but also chemically crosslinked, thus greatly improving the degree of crosslinking and mechanical properties between the long fibers and balancing the transverse and longitudinal tensile mechanical properties of the long fiberboard. When applied to automotive body underbody panels, engine compartment underbody panels, battery underbody panels, mudguards, trunk trim panels, and front trunk panels, it retains the integrity of the fibers, forms a multi-porous structure, has good sound absorption, and high strength; at the same time, the product has good toughness and good resistance to stone impact. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the synthetic routes for maleimide diol and furan diol;
[0026] Figure 2 The 1H NMR spectrum of maleimide diol;
[0027] Figure 3 This is the 1H NMR spectrum of furan diol. Detailed Implementation
[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.
[0030] The raw materials used in the examples and comparative examples are described below:
[0031] PET#1: Yizheng Chemical Fiber, grade BG85, intrinsic viscosity 0.879 dL / g, melting point 248℃;
[0032] PET#2: Yizheng Chemical Fiber, grade FG600, intrinsic viscosity 0.67 dL / g, melting point 262℃;
[0033] Nucleating agent: Metal salt nucleating agent, potassium 2,2-dimethylolpropionate;
[0034] PEN: Polyethylene naphthalate, TN8065S, melting point 265℃, Teijin, Japan;
[0035] Ethylene glycol: analytical grade, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0036] 3-Amino-1,2-propanediol: 97%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0037] Glyceryl ether: 96%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0038] Pentaerythritol: 99%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0039] Sorbitol: 99.5%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0040] Terephthalic acid: 99%, Guangzhou Yuanda New Materials Co., Ltd.;
[0041] 2-Maleiminoacetic acid: 97%, Shenzhen Polymer Biochemical Technology Co., Ltd.;
[0042] Furfuralamine: 99%, Qiyuan (Guangdong) Pharmaceutical & Chemical Co., Ltd.;
[0043] NHS: N-hydroxysuccinimide, commercially available;
[0044] EDC·HCl: 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, commercially available;
[0045] Maleimide diol: Prepared in-house, preparation method as follows:
[0046] S1. Under a nitrogen atmosphere, dissolve 0.1 mol of 2-maleimide glycolic acid in 500 mL of anhydrous DMF and place the solution in a dry round-bottom flask. Add 0.12 mol of NHS and cool the flask to 0-4°C in an ice-water bath. While stirring, add 0.12 mol of EDC·HCl in portions, maintaining the ice bath temperature, and continue stirring for 30-45 minutes to fully activate the carboxyl groups into NHS esters. Add 0.11 mol of... 3-Amino-1,2-propanediol was dissolved in 100 mL of anhydrous DMF and slowly added dropwise to the activated acid solution. Simultaneously, 0.2 mol of triethylamine was added to neutralize the HCl produced in the reaction. The reaction system was allowed to rise naturally to room temperature and stirred in the dark for 2-4 hours. The reaction progress was monitored using TLC (thin-layer chromatography) until the starting acid was almost completely eliminated. After the reaction was complete, the reaction solution was poured into 100 mL of ice water, and the product was extracted three times with 300 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation under reduced pressure to obtain the crude product. The crude product was purified by silica gel column chromatography using a 10:1 ethyl acetate / n-hexane eluent system. The target fraction was collected, and after rotary evaporation, maleimide diol was obtained. The structure of the product was determined using deuterated chloroform (CDCl3) as the solvent. Figure 2 As shown in the diagram. The schematic diagram of the synthetic route for maleimide diol is shown below. Figure 1 As shown.
[0047] Furandiol: Prepared in-house, the preparation method is as follows:
[0048] In a nitrogen atmosphere, 0.1 mol of furfurylamine was added to a flask, followed by 20 mL of anhydrous ethanol. The mixture was stirred to dissolve, forming a clear solution. Glyceryl ether was slowly added dropwise to the furfurylamine solution using a constant-pressure dropping funnel (dropping rate controlled at 1 drop / second, with stirring maintained at 300-500 rpm). After the addition was complete, the reaction temperature was maintained at 50℃ for 2-6 hours (monitored by thin-layer chromatography (TLC), with ethyl acetate:petroleum ether as the developing solvent). After the reaction, the reaction solution was transferred to a rotary evaporator, and the solvent was removed by evaporation at 40℃ and 0.08 MPa vacuum, yielding a pale yellow viscous liquid. The liquid was purified by column chromatography (silica gel column, eluent: ethanol:dichloromethane = 1:10). The target fraction was collected and then rotary evaporated again to obtain furan glycol. The structure of the product was determined using deuterated chloroform (CDCl3) as the solvent. Figure 3 As shown.
[0049] The schematic diagram of the synthetic route for furan diol is shown below. Figure 1 As shown.
[0050] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.
[0051] Preparation Example
[0052] Polyester leather 1-8
[0053] Modified polyesters 1-8: Preparation methods are as follows:
[0054] Pre-dried terephthalic acid, polyol, furan glycol, maleimide glycol, and antimony trioxide catalyst were added to a 100L stainless steel premixing tank equipped with a stirrer. The specific components are shown in Table 1. The amount of antimony trioxide added was 1 mol% of the total molar amount of the monomers. The mixture was stirred at 200 rpm for 30 min to ensure initial homogeneity of the solid raw materials. Then, ethylene glycol was added, and stirring continued for 15 min to form a homogeneous mixture. The mixture was transferred to a reaction vessel, and nitrogen was introduced to purge the air from the vessel three times, maintaining a nitrogen flow rate of 50 L / min. Stirring was started at 300 rpm, and the electric heating mantle was activated to raise the temperature to 180°C at a rate of 5°C / min, initiating the esterification reaction. During the reaction, the distilled water and ethylene glycol vapors were collected through a reflux condenser and condensed before entering a water separator. The separated ethylene glycol could be recycled. The esterification reaction lasts for 8-10 hours. During this period, the acid value of the system is measured every hour. When the acid value drops to 50-80 mg KOH / g, the esterification reaction is considered to be basically completed.
[0055] After the esterification reaction is complete, gradually increase the reaction temperature to 260-280℃, while simultaneously starting the vacuum system to slowly reduce the pressure inside the reactor. Reduce the pressure from atmospheric pressure to 100 Pa within 0.5 hours, and then gradually reduce it to below 10 Pa within 2 hours to promote the discharge of small molecule byproducts. During the polycondensation reaction, closely observe the changes in stirring torque and adjust the stirring rate appropriately (350-450 r / min) to ensure thorough mixing of the materials and prevent rod climbing. The polycondensation reaction continues for 4-6 hours. The reaction endpoint is determined by measuring the intrinsic viscosity of the system (after sampling, dissolve in a phenol-tetrachloroethane mixture and measure using an Ubbelohde viscometer). Stop the reaction when the intrinsic viscosity reaches 0.6-0.8 dL / g.
[0056] After the reaction is complete, turn off the heating and vacuum systems, and introduce nitrogen gas into the reactor until the pressure reaches atmospheric pressure.
[0057] The hydraulic discharge device was activated to extrude the molten polyester through a gear pump, followed by pelletizing with a pelletizer to obtain polyester granules. The polyester granules were then placed in a fluidized bed dryer and dried at 120°C under a nitrogen atmosphere for 6 hours to remove residual small molecules and reduce the moisture content to below 0.05%, thus obtaining modified polyester. The modified polyester underwent the following performance tests, and the results are shown in Table 1:
[0058] Melting point determination: The melting point of polyester was determined according to Method B of GB / T 14190-2017 "Test Method for Melting Point of Fiber Grade Polyester (PET) Chips" 5.3. Differential scanning calorimeter (DSC) was used with a heating rate of 10℃ / min.
[0059] Intrinsic viscosity test: According to GB / T 14190-2017 "Test Methods for Intrinsic Viscosity of Fiber Grade Polyester (PET) Chips" 5.1 Test Method A, the intrinsic viscosity was measured using an Ubbelohde viscometer, with phenol / 1,1,2,2-tetrachloromethane (mass ratio 50:50) as the solvent.
[0060] End group content determination: The end carboxyl content of polyester was determined by volumetric titration according to Method A of Test Method 5.4 for End Carboxyl Groups in GB / T 14190-2017 "Test Methods for Fiber Grade Polyester (PET) Chips".
[0061] Table 1. Monomer addition amount (molar parts) of modified polyester
[0062]
[0063]
[0064] Weigh 100 parts by weight of modified polyester 1-8 and mix with 2 parts by weight of carbon black, extrude through a twin-screw extruder, and pelletize to obtain polyester skin material 1-8.
[0065] Polyester core layer
[0066] As shown in Table 2, the polyester core material is mixed according to the formula, extruded through a twin-screw extruder, and pelletized to obtain the polyester core material.
[0067] The polyester core material underwent the following performance tests, and the results are shown in Table 2:
[0068] Melting point determination: The melting point of polyester was determined according to Method B of GB / T 14190-2017 "Test Method for Melting Point of Fiber Grade Polyester (PET) Chips" 5.3. Differential scanning calorimeter (DSC) was used with a heating rate of 10℃ / min.
[0069] Intrinsic viscosity test: According to GB / T 14190-2017 "Test Methods for Intrinsic Viscosity of Fiber Grade Polyester (PET) Chips" 5.1 Test Method A, the intrinsic viscosity was measured using an Ubbelohde viscometer, with phenol / 1,1,2,2-tetrachloromethane (mass ratio 50:50) as the solvent.
[0070] Table 2 Composition and proportions of polyester core material (parts by weight)
[0071] Polyester core layer 1 Polyester core layer 2 Polyester core layer 3 Polyester core layer 4 PET#1 80 PET#2 80 100 80 PEN 20 20 20 nucleating agent 1 1 1 carbon black 2 2 2 2 Melting point (°C) 265.8 251.1 263.5 263.1 Viscosity (dL / g) 0.82 0.71 0.77 0.74
[0072] Examples and Comparative Examples
[0073] A long fiber with a core-sheath structure includes a polyester sheath layer and a polyester core layer. The composition and formulation of the polyester sheath layer and the polyester core layer are shown in Table 3. The preparation method of the long fiber with the core-sheath structure includes the following steps:
[0074] S1. The polyester skin material and the polyester core material are melt-extruded separately in a twin-screw extruder to obtain polyester skin chips and polyester core chips;
[0075] S2. The polyester sheath chips and polyester core chips are vacuum dried at 150℃ for 5 hours. The polyester sheath chips are melted in a screw extruder at 160-250℃ with the melt pressure controlled at 8-12MPa. The polyester core chips are melted in another extruder at 260-270℃ with the melt pressure controlled at 10-15MPa. After filtration, the two melts are fed into the composite spinning assembly with precise flow control (ensuring the sheath-core ratio is 1:3) through a metering pump. After being fused into a concentric structure in the spinneret orifice, they are extruded to form nascent fibers with a diameter of 80μm.
[0076] S3. The nascent fibers are rapidly cooled to 80-100℃ by side blowing air to solidify the core-sheath structure. Then, they are put into a stretching machine and stretched in multiple stages at 80-120℃, with a total stretching ratio of 3-5 times, to orient the molecular chains and improve the fiber strength.
[0077] S4. Finally, heat set in an oven at 120-180℃ to eliminate internal stress, and then wind at a speed of 3000-5000m / min to finally obtain long fibers with a core-sheath structure.
[0078] The long fibers of the examples and comparative examples were subjected to the following performance tests, and the results are shown in Table 3.
[0079] Monofilament breaking strength: The breaking strength of the long fiber was tested according to GB / T 14344-2022 Test Method for Tensile Properties of Chemical Fiber Filaments, with the moving clamp speed at 500 mm / min;
[0080] Table 3 Composition of long fibers and monofilament breaking strength
[0081] Polyester leather Polyester core layer Single filament breaking strength (cN / dtex) Example 1 Polyester leather 1 Polyester core layer 1 3.87 Example 2 Polyester leather 2 Polyester core layer 1 4.36 Example 3 Polyester leather 3 Polyester core layer 1 3.95 Example 4 Polyester leather 4 Polyester core layer 1 3.8 Example 5 Polyester leather 2 Polyester core layer 2 3.62 Comparative Example 1 Polyester leather 5 Polyester core layer 1 2.69 Comparative Example 2 Polyester leather 6 Polyester core layer 1 4.57 Comparative Example 3 Polyester leather 7 Polyester core layer 1 4.8 Comparative Example 4 Polyester leather 8 Polyester core layer 1 2.01 Comparative Example 5 PET#1 Polyester core layer 1 2.42 Comparative Example 6 Polyester leather 2 Polyester core layer 3 3.07 Comparative Example 7 Polyester leather 2 Polyester core layer 4 2.82
[0082] Application Examples 1-12
[0083] A long fiberboard, prepared from long fibers with a core-sheath structure obtained in Examples 1-5 and Comparative Examples 1-7, is made by means of the following steps:
[0084] Long fibers with a core-sheath structure are arranged transversely and longitudinally to form a felt, which is then fed above a mold and clamped by a heated mold. Steam at 1.6 MPa is introduced to rapidly penetrate the fibers, and the mold is opened after holding the pressure for 11 seconds. The long fiberboard is then removed, cooled, and punched. The areal density of the long fiberboard is 1200 g / m². 2 .
[0085] Application Example 13
[0086] PP fiberglass board, density 1600g / m³ 2 It is obtained by injection molding from 100 parts by weight of polypropylene and 20 parts by weight of glass fiber;
[0087] The obtained long fiberboard was subjected to the following performance tests, and the results are shown in Table 4:
[0088] (1) Tensile strength: The longitudinal and transverse tensile strengths of fiberboard and PP fiberglass board were tested in accordance with the standard ISO 527-1:2019 "Plastics - Determination of tensile properties".
[0089] (2) Impact toughness: The impact toughness of fiberboard and PP fiberglass board was tested in accordance with the standard ISO 179-1:2023 "Determination of Charpy impact properties of plastics - Non-instrumental impact test".
[0090] (3) Mechanical properties after water absorption: The fiberboard and PP fiberglass board were placed in a 40℃ water tank for 240h to absorb water and deteriorate. Their longitudinal tensile strength and transverse tensile strength were tested again.
[0091] Table 4 Mechanical property tests of long fibers
[0092]
[0093]
[0094] The test results from the preparation examples, embodiments, and application examples show that introducing polyols into the polyester molecular chain to form a branched structure, and introducing furan and maleimide side chains into the polyester, can disrupt the regularity of the polyester molecular chain, lower its melting point, and allow for rapid melting during compression molding, shortening heating time and saving energy. Furthermore, the reversible reaction between furan and maleimide groups improves the adhesion strength between the surface of a single fiber and the fiberboard interface without affecting the rapid melting of the polyester skin. However, excessive crosslinking density can easily lead to a decrease in the impact toughness of the fiberboard. Similarly, the number of branches in the modified polyester molecular structure needs to be controlled within a certain range. Excessive branching reduces the viscosity of the polyester skin, negatively impacting mechanical properties. Simultaneously, increased terminal hydroxyl content leads to increased water absorption, which can easily result in deteriorated mechanical properties after water absorption.
[0095] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A long fiber having a core-sheath structure, characterized in that, The product comprises a polyester sheath and a polyester core. The polyester sheath, by weight, comprises 100 parts modified polyester and 0-5 parts colorant. The modified polyester is obtained by polymerization of a diacid monomer and a polyol monomer in a molar ratio of 1:(1.0-1.5). The diacid monomer includes one or more of terephthalic acid and isophthalic acid. The polyol monomer, by molar weight, comprises 70-110 parts ethylene glycol, 2-10 parts polyol having 3-6 hydroxyl groups, 5-10 parts maleimide diol, and 5-10 parts furan diol. The structural formula of the maleimide diol is shown in Formula 1, and the structural formula of the furan diol is shown in Formula 2. The polyester core layer comprises the following components by weight: 80-100 parts PET, 10-20 parts PEN, 0.1-1 parts nucleating agent, and 0-5 parts colorant.
2. The long fiber with a core-sheath structure as described in claim 1, wherein the mass ratio of the sheath to the core is 1:(3-5).
3. The long fiber with a core-sheath structure as described in claim 1, characterized in that, The nucleating agent is at least one of talc, organic amides, and hydroxyalkyl metal salts; the colorant is carbon black; and the polyol is selected from at least one of glycerol, pentaerythritol, xylitol, dipentaerythritol, and sorbitol.
4. The long fiber with a core-sheath structure as described in claim 1, characterized in that, The preparation method of the maleimide diol is as follows: 2-maleimide acetic acid and 3-amino-1,2-propanediol are condensed in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
5. The long fiber with a core-sheath structure as described in claim 1, characterized in that, The furan glycol is prepared by reacting pre-dried furfurylamine and glycidyl ether at 25–50°C for 2–24 hours.
6. The long fiber with a core-sheath structure as described in claim 1, characterized in that, The modified polyester is prepared as follows: diacid, polyol, and catalyst are added to a reaction vessel in a certain proportion, stirred evenly, and then heated to 170-190℃ for esterification reaction. The reaction lasts for 8-10 hours. When the acid value drops to 50-80 mg KOH / g, the esterification reaction is considered to be basically completed. The reaction temperature is gradually increased to 260-280℃, and the vacuum system is started simultaneously to slowly reduce the pressure inside the reaction vessel to below 10 Pa for polycondensation reaction. When the intrinsic viscosity reaches 0.35-0.8 dL / g, the reaction is stopped, nitrogen gas is introduced to atmospheric pressure, and the molten polyester is extruded through a gear pump, granulated by a pelletizer, and dried to obtain the modified polyester.
7. A method for preparing a long fiber with a core-sheath structure as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. The polyester skin material and the polyester core material are melt-extruded separately in a twin-screw extruder to obtain polyester skin chips and polyester core chips, which are then pre-dried. S2. The polyester sheath chips are melted in a screw extruder at 160-250℃, with the melt pressure controlled at 8-12MPa. The polyester core chips are melted in another extruder at 260-270℃, with the melt pressure controlled at 10-15MPa. After filtration, the two melts are fed into the composite spinning assembly with precise flow control through a metering pump. After being combined into a concentric structure in the spinneret orifice, they are extruded to form nascent fibers with a diameter of 50-100μm. S3. The nascent fibers are rapidly cooled to 80-100℃ by side blowing air to solidify the core-sheath structure, and then enter the stretching machine for multi-stage stretching at 80-120℃, with a total stretching ratio of 3-5 times. S4. Finally, heat set in an oven at 120-180℃ and wind at a speed of 3000-5000m / min to obtain long fibers with a core-sheath structure.
8. A long fiberboard, characterized in that, The long fiberboard is prepared by compression molding of the core-sheath structure as described in any one of claims 1 to 6, wherein the areal density of the long fiberboard is 1200–1600 g / m³. 2 .
9. The method for preparing long fiberboard as described in claim 8, characterized in that, The process includes the following steps: long fibers with a core-sheath structure are arranged in a transverse and longitudinal pattern to form a felt, which is then fed to a mold and clamped by a heated mold. Steam at 1.4–1.8 MPa is introduced to quickly penetrate the fibers. The mold is opened after holding the pressure for 8–15 seconds, the long fiberboard is removed, and the material is cooled and punched.
10. The application of the long fiber as described in any one of claims 1 to 6 and the long fiberboard as described in claim 8 in the underbody protection plate, engine compartment underbody protection plate, battery underbody protection plate, mudguard, trunk trim panel, and front trunk panel of an automobile.
Citation Information
Patent Citations
Preparation method for UV-curing self-healing polyurethane based on furan-maleimide structure
CN105348474A
Filament low-melting-point polyester fiber and preparation method thereof
CN106757518A
High polymer bonded explosive with self-repair function and preparation method thereof
CN108329184A
Skin-core type foaming polyester fiber and preparation method thereof
CN119932755A
Glass fiber-containing resin composition, and cured product
JP2021095532A